The effect of organizational uprightness behaviors on organizational brilliance through the mediation of pioneer vigilance: analytical research of the opinions of a sample of administrators at the national retirement authority - Baghdad - Ibrahim, Shamael Abdul Karim; Hussein, Maysoon Ali (Edelweiss Applied Science and Technology, 2024)
The study aimed to determine the effect of Organizational Uprightness Behaviors with its dimensions (empathy, trust, integrity, optimism) in Organizational Brilliance with its dimensions (leadership Brilliance, service Brilliance, creativity, knowledge Brilliance) by mediating the Pioneer Vigilance with its dimensions (survey and research, cooperation and communication, evaluation, and judgment) in the National Retirement Authority in Baghdad. The descriptive analytical approach was adopted for the purpose of the study in the research community, by distributing a questionnaire to a random sample of (169) individuals suitable for analysis from the total community of (328) individuals, represented by a group of employees in the Authority, by adopting the questionnaire as a primary tool in collecting data Statistical programs were used to analyze the data, including (Smart Pls 4, SPSS, v.28, AOMS, and V26). The research attempted to answer several questions that express the research problem, the most important of which was: Is there an impact of organizational uprightness behaviors in achieving organizational Brilliance mediated by pioneer vigilance? The importance of applying the research in the Iraqi National Retirement Authority lies in the fact that it is one of the critical organizations that target a broad segment of Iraqi society who have spent their youth-serving the country and who deserve to find the best ways to serve them and complete their transactions with all respect and appreciation, and facilitate procedures as quickly as possible. The validity of the hypotheses that stated the existence of a significant and statistical effect of organizational uprightness behaviors on organizational Brilliance was proven, and pioneer vigilance has a clear role in enhancing the size of this effect through partial mediation. The results indicate that the number and quality of publications in Organizational Uprightness Behaviors, Pioneer Vigilance, Organizational Brilliance contribute deeply to enriching and rooting this trend, in addition to the need to encourage platforms and climates for research and authorship in this vital and relevant field.